Устойчивость оболочек вращения из зернистых композитных материалов при длительной повреждаемости компонентов - Хорошун, Л.П.; Бабич, Д.В. (Прикладная механика, 2010)
Виконано постановку, наведено методику та дано розв’язок задачі про біфур- каційну стійкість оболонок обертання із зернистих композитних матеріалів при врахуванні довготри- валої пошкоджуваності компонентів. The statement is done, the technique is represented and the solution is given for the problem on bifurcational stability of shells of revolution made of granular composite materials with allowance for the long-term damage of components.